2018
DOI: 10.1159/000494652
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Exosomes Reduce A1 Astrocytes via Downregulation of Phosphorylated NFκB P65 Subunit in Spinal Cord Injury

Abstract: Background/Aims: Neurotoxic A1 astrocytes are induced by inflammation after spinal cord injury (SCI), and the inflammation-related Nuclear Factor Kappa B (NFκB) pathway may be related to A1-astrocyte activation. Mesenchymal stem cell (MSC) transplantation is a promising therapy for SCI, where transplanted MSCs exhibit anti-inflammatory effects by downregulating proinflammatory factors, such as Tumor Necrosis Factor (TNF)-α and NFκB. MSC-exosomes (MSC-exo) reportedly mimic the beneficial effects of MSCs. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(128 citation statements)
references
References 83 publications
7
121
0
Order By: Relevance
“…BMSCs-derived exosomes were extracted as previously reported [28], and the morphology and size distribution of exosomes were observed by transmission electron microscopy and dynamic light scattering (DLS) analysis. The exosome markers were assessed by Western blot analysis.…”
Section: Extraction Identification and Labeling Of Exosomesmentioning
confidence: 99%
“…BMSCs-derived exosomes were extracted as previously reported [28], and the morphology and size distribution of exosomes were observed by transmission electron microscopy and dynamic light scattering (DLS) analysis. The exosome markers were assessed by Western blot analysis.…”
Section: Extraction Identification and Labeling Of Exosomesmentioning
confidence: 99%
“…EVs are emerging as a promising tool for therapeutic delivery owing to its favorable intrinsic features of biocompatibility, stability, stealth capacity, and the ability to overcome natural barriers (Dostert et al 2017;Shahjin et al 2019). In other studies, bm-SC-EVs were found to exert immune-suppressive effects by enforcing ARM macrophage polarization and stimulating T-cell induction as well as producing neurotrophic factors and anti-inflammatory cytokines, as a dedicated reaction of environmental vesicles or cytokines from degenerating, malfunctioning cells (Dostert et al 2017;Cizkova et al 2018;Harting et al 2018;Kim et al 2018;Wang et al 2018;Beers and Appel 2019;Shahjin et al 2019). This hypothesis, though, is still a hypothesis, and recently, the possibility that bm-SCs one way or the other might donate healthy mitochondria to neurons that harbor dysfunctional mitochondria has also been raised to explain their positive effects (Babenko et al 2015).…”
Section: Mode Of Action Of Bm-derived Stromal Cellsmentioning
confidence: 99%
“…A reduction of the inflammatory response was observed by Kim et al too [184,185]. A diminished inflammation was even observed in spinal cord injury, probably via neuronal apoptosis inhibition, angiogenesis stimulation, A1 astrocytes inactivation and up-regulation of anti-inflammatory IL-10 and TGF-β as well as down-regulation of the pro-inflammatory TNF-α and IL-1β [171,[186][187][188][189]]. An essential function after spinal cord injury and brain ischemia was also attributed to the miRNA-113b [184,190].…”
Section: Extracellular Vesicles-based Regenerative Medicinementioning
confidence: 88%